T-satisfiability test problem for the VL1 logical language of the VRS system - Timofeev, V.G. (Інститут програмних систем НАН України, 2015)
In this paper we give a short introduction to the satisfiability modulo theories (SMT) problem and demonstrate how the methods developed in the SMT research field can be applied in the requirement verification tool VRS, which supports insertion modelling methodology. We formalize the logical language VL1 used for formal reasoning in VRS and justify decidability of satisfiability problem in that language. Besides we discuss the context of the problem being solved and indicate possible methods that can be used on different stages of solution. Finally, we present a satisfiable conjunction search method, which is based on a set-representation of logical connectives in formulas.